EFEKTIVITAS MODEL PEMBELAJARAN GAME BASED LEARNING TERHADAP HASIL BELAJAR SISWA: LITERATURE REVIEW - Azizah, Batrotul; Widoyoko, Sugeng Eko Putro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Improving student learning outcomes remains a major concern in education. Various learning innovations continue to be developed, one of which is through the implementation of Game Based Learning (GBL), which integrates game elements into learning activities. This study aims to analyze the effectiveness of Game Based Learning (GBL) implementation in improving student learning outcomes. This study uses a literature review method by analyzing 10 articles from national journals accredited with Sinta 3 and 4 published in the 2023-2025 period. The research data sources were obtained through an article search process using the Google Scholar database. The selected articles were then analyzed descriptively to identify findings related to the effectiveness of Game Based Learning (GBL) on student learning outcomes. The analysis results show that Game Based Learning (GBL) has a positive influence on student learning outcomes in various subjects and educational levels. These findings consistently indicate an increase in learning outcomes after the implementation of Game Based Learning (GBL). The success of Game Based Learning (GBL) implementation is evident in improved learning outcomes, learning completeness, and increased student engagement during the learning process. Furthermore, the use of various digital media and platforms in Game Based Learning (GBL) implementation contributes to more engaging, interactive, and enjoyable learning for students. These findings demonstrate that Game Based Learning (GBL) is an effective learning model for improving student learning outcomes in a variety of learning environments.